Suplementasi Ekstrak Buah Asam Kandis (Garcinia xanthochymus) dalam Air Minum sebagai Acidifier: Pengaruh terhadap Profil Darah dan Diferensiasi Leukosit Puyuh Jepang (Coturnix coturnix japonica): Supplementation of Sour Mangosteen (Garcinia xanthochymus) Fruit Extract in Drinking Water as an Acidifier: Effects on Blood Profile and Leukocyte Differentiation in Japanese Quails (Coturnix coturnix japonica) - Sakti, Tri Yuda; Suharti, Sri; suci, dwi margi (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2024)
Organic acids, including those found in sour mangosteen (Garcinia xanthochymus) fruit extract, have the potential as alternatives to antibiotics. This study aimed to evaluate the effect of sour mangosteen fruit extract (SME) supplementation at different acidity levels (pH 4, pH 3, and pH 2) as an acidifier on the blood profile and leukocyte differentiation of adult female Japanese quails (Coturnix coturnix japonica). A completely randomized design (CRD) was applied with four treatments: a control without SME supplementation (P0) and groups receiving SMFE-supplemented drinking water adjusted to pH 4 (P1), pH 3 (P2), and pH 2 (P3). Each treatment was replicated three times with 11 heads per replicate. The extract was administered twice weekly from 6 to 12 weeks of age. All quails were fed a commercial layer diet containing 20% crude protein, 4% crude fat, 6% crude fiber, 4% calcium, and 0.6% total phosphor. The observed parameters included blood profile indices (erythrocytes, hemoglobin, hematocrit, leukocytes) and leukocyte differentiation (lymphocytes, monocytes, heteropils, and neutrophils). The results indicated that SME supplementation at pH 4, pH 3 and pH 2 in drinking water did not significantly affect the blood profile or leukocyte differentiation. These finding suggest that Garcinia xanthochymus fruit extract at these acidity levels can be effectively utilized as an acidifier in drinking water.